MARIA’S STRUGGLES THROUGH BOUNDARY SITUATIONS TO BE AN AUTHENTIC INDIVIDUAL IN PAULO COELHO’S ELEVEN MINUTES NOVEL - NINGRUM, AFIDA ROSDIANA (Jurnal Ilmiah Mahasiswa FIB, 2013)
The questions about human existence and their action to maintain their existence are the central notion of existentialism. The writer conducted a study about human existence in Eleven Minutes novel which shows the struggles of Maria as the main character in revealing her authentic self through boundary situations as portrayed in Paulo Coelho’s novel Eleven Minutes. This study belongs to qualitative research which Existentialism approach was used to guide the writer to keep her study focus on existentialism fields in analyzing phenomena happened in the novel related with the research problem. This study reveals that Maria has passed through boundaries in her life to be an authentic individual. She flies to Geneva inexperience, decides to become a prostitute, and gets addicted to pain as source of pleasure and struggle to conquer her own self of love. Even though she has to maintain pain, suffering, guilt, and struggling, she has succeeded to find her authentic self. Maria has her own freedom and decision toward things in her life. She takes the consequences and in the other side, she is aware that there is another more powerful being which is beyond her grasp. It is the transcendence.   Keywords: struggles, authentic individual, existence, boundary situations, transcendence